Greek Foreign Policy and the Community of International Relations Scholars - Constas, Dimitri (Études helléniques / Hellenic Studies, 1997)
Is the period from 1974 to 1996 domestic sources have played an important role in the formulation of Greek foreign policy. The community of International Relations scholars, however, has failed to become a respected, autonomous factor in influencing foreign policy due to the neglect of theory, emphasis on superficial, short-term, policy-related analyses and its fragmentation. Consequently, some notable exceptions notwithstanding, Greek I.R. scholars, rather than introducing an independent perspective based on the wealth of knowledge accumulated in the scholarly work of the International Relations community, endorsed views reflecting ideological and political divisions in Greek society or narrow professional interests. Greek policy-makers and the community of I.R. scholars must join forces in addressing the country’s central foreign policy dilemma:how the diversion of scarce resources to the attainment of a level of economic development that will Bring Greece to the path of European integration will not cause irreparable damage to the country’s security in view of the very real Turkish threat. The community of I.R. scholars can only meet this challenge by putting aside artificial categorizations into “Europeanists” and “Nationalists” and reestablish confidence in International Relations as a scientific field of study. Otherwise it runs a real risk of marginalization to the detriment of its members and of the country as a whole.